Diagnosis of Ocular Toxocariasis: a case report: Poster Presentation - Case Report - Resident - Irene Carolin Mulyadi; Ivonne Ramenusa; Josef Sem Berth Tuda; Melissa Ratag (Majalah Oftalmologi Indonesia, 2023)
Introduction : Ocular toxocariasis (OT) is an eye parasitosis due to incidental ingestion of Toxocara cati or canis larvae. Although mostly affects young children, it can also occur in older individuals. It is usually uniocular with various presentations. Case Illustration : A 69-year-old woman came with a chief complaint of deteriorating vision and pain in her left eye (LE)2 weeks prior to the visit, accompanied by floaters, redness, itchiness, and glare. She had a contact history with neighborhood dogs. Her best corrected visual acuity (VA) was 6/12 in the right eye (RE) and 3/60 in the LE. The intraocular pressure of LE was 27mmHg. Examinations of the LE found corneal edema, keratic precipitates, worm-like foreign bodies that moved in the anterior chamber, lens and vitreous opacity, and obscured fundus. The ultrasound showed a membrane-like lesion and no vitreomacular traction. The examination of the RE was unremarkable. We performed prompt foreign body extraction with local anesthesia and prescribed oral albendazole, topical and oral antibiotics, and steroids afterward. The investigation of the specimen revealed Toxocara larvae. There was no VA improvement after 1 month of close observation. Discussion : The OT diagnosis is based on clinical findings and a history of exposure to dogs or cats, soil, and consuming raw or undercooked meat. The gold standard for diagnosis is specimen biopsy. While no acceptable treatment regimen exists, the combination of anthelmintics and corticosteroids appears useful in some cases. Conclusion : Clinical presentation, parasitologic confirmation, and close contact with pets may be key elements to making the diagnosis.